Ozonized oils: a review of its quality control, stability and effectiveness in the treatment of Acne vulgaris - Teixeira, Gabriela; Ondina, Stacy; Cruz, Alexandre Bella; Bellé Bresolin, Tania Mari (Drug Analytical Research, 2026)
Acne affects most young people and its topical treatment with antibacterials is associated with increased bacterial resistance to antibiotics and adverse effects. As an alternative, ozone therapy stands out through the application of ozonized oils. The objective of this work was to raise the scientific evidence about the effectiveness in the treatment of acne, in addition to the techniques of characterization and stability of ozonated oils. This is an exploratory, descriptive study with a quantitative approach, based on the analysis of scientific references in a bibliographic review of the expository type, of the last 20 years. Among the selected references, only four manuscripts reporting clinical studies of ozone therapy, with controversial results. Seven articles with the physicochemical characterization of ozonated oils were found. The major part of manuscripts reported the use of sunflower, sesame and olive oil. The more common techniques used to characterize the ozonation process are the peroxide value (PV) and the iodine index (Ii), which represents the proportion of unsaturated groups, whose values increase and decrease, respectively with ozonization progress. The viscosity of oils is increased by the formation of polymeric peroxides; the FTIR spectrum, which identifies the decrease in the stretch bands C = C, in addition to ozone formation, monitored by NMR, are also employed. Increased antimicrobial activity has been demonstrated with the ozone level of the oils, but the activity against Cutibacterium acne has not been reported. Only two article reported satisfactory stability for 6 months of refrigerated ozonized oil or kept at room temperature, showing the need for more specific research to support the application of ozonized oils in the treatment of acne and stability data of these products.